Effects of early sports specialization on landing and balance ability in female college basketball players - Kona, K.; Nagano, Y.; Sasaki, S.; Suzukawa, M. (The Physician and Sportsmedicine, 2025)
Objectives Early specialization in a single sport from childhood is associated with an increased risk for acute and overuse injuries. Conversely, experience in multiple sports may be associated with improved neuromuscular control and performance. Currently, early sports specialization remains poorly researched in Japan. Therefore, this study aimed to clarify the relationship between early sports specialization and landing and balance ability in Japan.